HUBUNGAN KEBERADAAN BREEDING PLACE DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KOTA SEMARANG DAN SEKITARNYA - Muhammad Adib Mubarok; Nur Endah Wahyuningsih; Anto Budiharjo (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue Hemorrhagic Fever is an infectious disease caused by dengue virus that is transmitted through Aedes mosquito bites, both Aedesaegypti and Aedesalbopictus. DHF is one of the major public health problem in Indonesia.The Incidence Rate (IR) of DHF in Semarang City from 2006 to 2016 are always much higher than IR DHF of Central Java and IR DHF of National Indonesia.The cases of Dengue Hemorrhagic Fever (DHF) in Semarang City has increased significantly and cause death.This study aims to see the Breeding Places description and its relation to the incidence of Dengue Hemorrhagic Fever in Semarang city and surrounding areas.The type of research was an observational analytic study using Case-control design. The cases sample in this study were hospitalized DHF patients from the period of March to May 2017 in three hospitals in Semarang City.The control samples were health people and live around the cases with the same characteristics. Total sample were 27 cases and 27 controls. The data was analyzed by Mann Whitney test.The result showed that insignificant factors were existence of daily necessities containers (p=0,383), existence of containerswhat are not daily necessities (p=0,307), existence of total containers (p=0,142), opened containers condition (p=0,199), closed containers condition (p=0,683), and containers infested with larvae (p=0,253).  In conclusion, there is no association between breeding places factors with DHF incidence in Semarang city and surrounding areas.